Vulvar lichen sclerosus in an 8-year-old girl. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Case report. An 8-year-old girl was first observed due to vulva paresthesiae dating from six months. She had performed a skin biopsy not helpful from a diagnostic point of view. The clinical picture at the time of the first observation (Fig. 1) was diagnostic for lichen sclerosus showing on the labia majora and the surrounding skin a white, shiny skin and on the left labium majus white micropapules; moreover, above and also in close vicinity to the right labium minus three hemorrhagic points were evident. Therapy as needed with methylprednisolone aceponate and tacrolimus alternately was prescribed in case of symptoms. Both drugs proved useful in reversing the symptoms and the raised papules (Fig. 2). After a bike ride a widespread blood suffusion appeared on the right labium majus (Fig. 3), confirming the clinical diagnosis of lichen sclerosus.